Genomic analysis of codon usage shows influence of mutation pressure, natural selection, and host features on Senecavirus A evolution. (November 2017) - Chen, Ye; Xu, Quanming; Tan, Chen; Li, Xinxin; Chi, Xiaojuan; Cai, Binxiang; Yu, Ziding; Ma, Yanmei; Chen, Ji-Long
Abstract: Senecavirus A (SVA) infection was recently confirmed in pigs in Brazil, United States of America and Canada. To better understand the molecular characteristics of isolated SVA genomes, we first reported genome-wide comprehensive analyses of codon usage and various factors that have contribute to the molecular evolution in SVA. The effective number of codons (ENC) ranged from 54.51 to 55.54 with an average of 54.87 ± 0.285, which reveals a relatively stable nucleotide composition. We found that codon usage bias of the SVA was low. Mutational pressure acted as an increasingly dominant factor for the evolution of the virus compared with the natural selection. Notably, codon usage bias was also affected by the geographic distribution and isolated time. The first systemic analysis on the codon usage bias of the SVA provides important information for the understanding of the evolution of the SVA and has fundamental and theoretical benefits. Highlights: We first reported genomic analysis of codon usage in SVA. Codon usage bias of the SVA was low. Mutational pressure was an increasingly dominant factor for the evolution of SVA.